Competition submission for the 'Pipe Dreams' album - Onwudinjo, Jennifer (My University, 2023)
Jazz is a genre that tends to pull its listener in. This is expressed by turning a two-dimensional surface into a three-dimensional experience. It visually draws the viewer into experiencing the album’s spirit and feeling. Creating this illusion of depth is done with the use of layers. Each layer represents a single note in music and when layered they make a beautiful composition.
Presented on April 20, 2023 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: package design; album design